Artificial Intelligence and the Ethics of Tafsir: Integrating Digital Technologies and Islamic Humanities in Automating Interpretative Processes - Umar, Ahmad; Haqqi, Abdul; Rojihisawal, Faisal; Fitrah AR, Muhammad Dzul; Dewi, Deshinta A; Adnan, Abdulkareem (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study examines the multidisciplinary integration of Artificial Intelligence (AI), ethics, and interpretive studies in the context of Qur'anic exegesis (Tafsir). Methodology: A systematic literature review and critical analysis mapped the intersection of AI technologies and Tafsir studies. Data were collected from Scopus and ProQuest using relevant keywords. Selected literature was thematically analyzed to identify opportunities, challenges, and ethical issues. Comparative insights from other religious traditions contextualized findings within broader humanities and digital ethics perspectives and emerging interdisciplinary scholarship across academic contexts. Main Findings: AI techniques, particularly Natural Language Processing (NLP) and machine learning, hold considerable potential to enhance the efficiency, scalability, and accessibility of Qur'anic exegesis by processing large corpora of Tafsir, detecting patterns, and suggesting new interpretive pathways. At the same time, the study identifies critical risks, including data and model bias, reduction of interpretive depth, and the reconfiguration of scholarly authority and interpretive legitimacy. Key ethical concerns involve transparency, accountability, and safeguards against decontextualized or misleading interpretations that may conflict with established Islamic scholarly norms. Novelty/Originality of this study: This article proposes a cross-disciplinary framework integrating AI, Islamic studies, and ethics to conceptualize algorithmic Tafsir within digital Islamic humanities. It aligns AI’s technical capacities with Islamic ethical and hermeneutical principles, emphasizing collaborative governance among scholars. The study contributes to debates on responsible AI use and provides a structured foundation for future interdisciplinary research in Islamic digital scholarship.